Study on temperature and pressure pain sensation in the initial stage of invisible appliance - FANG Bin, LI Yuan, ZHOU Weina, YU Linfeng, ZHOU Meng, MA Junqing (Kouqiang yixue)
Objective To investigate the initial temperature sensation and pressure pain sensation in patients receiving invisible orthodontic treatment. Methods Twenty-two patients receiving clear aligner treatment(experimental group)and 22 volunteers(control group)participated. Perceptual changes were assessed using the visual analogue scale(VAS) and quantitative sensory testing(QST). The QST employed in this study included warm detection threshold/heat pain threshold (WDT/HPT), cold detection threshold/cold pain threshold (CDT/CPT), and pressure pain threshold (PPT). Tests were conducted on teeth 21 and 31, their gums, the left hand, and the left masseter muscle. Assessments occurred at baseline, 2 hours, 24 hours, 7 days, and 28 days after aligner placement. Results In the experimental group, VAS scores peaked at 24 hours and then significantly decreased(P<0.01). For teeth 21 and 31, the WDT and HPT of the labial attached gingiva, along with the PPT of these teeth, showed significant decreases at 24 hours and 7 days compared to baseline and the control group(P<0.01). At 24 hours and 7 days, VAS scores were negatively correlated with the WDT and HPT of the labial attached gingiva of teeth 21 and 31(P<0.05). Conclusion At 24 hours and 7 days post-clear aligner treatment, thermal sensitivity and pain, as well as pressure pain sensitivity, increased for the gingiva of teeth 21 and 31. Thermal sensitivity was also correlated with pain intensity.